Predicting the survival of patients with small bowel neuroendocrine tumours: comparison of 3 systems. Issue 2 (February 2017) - Clift, Ashley K; Faiz, Omar; Goldin, Robert; Martin, John; Wasan, Harpreet; Liedke, Marc-Olaf; Schloericke, Erik; Malczewska, Anna; Rindi, Guido; Kidd, Mark; Modlin, Irvin M; Frilling, Andrea
Abstract : Neuroendocrine tumours (NET) are clinically challenging due to their unpredictable behaviour. Nomograms, grading and staging systems are predictive tools with multiple roles in clinical practice, including patient prognostication. The NET nomogram allocates scores for various clinicopathological parameters, calculating percentage estimates for 5- and 10-year disease-specific survival of patients with small bowel (SB) NET. We evaluated the clinical utility of three prognostic systems in 70 SB NET patients: the NET nomogram, the World Health Organisation (WHO)/European Neuroendocrine Tumour Society (ENETS) grading system and the American Joint Commission on Cancer (AJCC)/Union Internationale Contre le Cancer (UICC) TNM staging method. Using Kaplan–Meier methodology, neither the WHO/ENETS grade ( P  = 0.6) nor the AJCC/UICC stage ( P  = 0.276) systems demonstrated significant differences in patient survival in the cohort. The NET nomogram was well calibrated to our data set, displaying favourable prediction accuracy. Harrel's C-index for the nomogram (a measure of predictive power) was 0.65, suggesting good prediction ability. On Kaplan–Meier analyses, there were significant differences in patient survival when stratified into nomogram score-based risk groups: low-, medium- and high-risk tumours were associated with median estimated survivals of 156, 129 and 112 months, respectively ( P  = 0.031). Our data suggest that a multivariable analysis-based NET nomogram may be clinically useful for patient survival prediction. This study identifies the limitations of the NET nomogram and the imperfections of other currently used single or binary parameter methodologies for assessing neuroendocrine disease prognosis. The future addition of other variables to the NET nomogram will likely amplify the accuracy of this personalised tool.